Book review: Lux, Claudia. Libraries on the agenda: Lobbying and advocating for library and information professionals - Elena Maceviciute (Information Research: An International Electronic Journal)
Lux, Claudia. Libraries on the agenda: Lobbying and advocating for library and information professionals. Berlin/Boston: Walter de Gruyter, 2024. xiv, 305 p. ISBN 978-3-11-079589-9